2016
DOI: 10.1038/ncomms12883
|View full text |Cite
|
Sign up to set email alerts
|

Wave-induced loss of ultra-relativistic electrons in the Van Allen radiation belts

Abstract: The dipole configuration of the Earth's magnetic field allows for the trapping of highly energetic particles, which form the radiation belts. Although significant advances have been made in understanding the acceleration mechanisms in the radiation belts, the loss processes remain poorly understood. Unique observations on 17 January 2013 provide detailed information throughout the belts on the energy spectrum and pitch angle (angle between the velocity of a particle and the magnetic field) distribution of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
204
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 145 publications
(221 citation statements)
references
References 28 publications
17
204
0
Order By: Relevance
“…Their relevance to the radiation belt dynamics has been evaluated in earlier works, based either on observations or model simulations (Albert & Young, 2005;Albert et al, 2009;Drozdov et al, 2015Drozdov et al, , 2017Shprits et al, 2006Shprits et al, , 2008Shprits et al, , 2016Shprits et al, , 2017Subbotin et al, 2010;Turner, Angelopoulos, Morley, et al, 2014;Usanova et al, 2014;Xiang et al, 2017;Xiao et al, 2010;Yu et al, 2013). Their relevance to the radiation belt dynamics has been evaluated in earlier works, based either on observations or model simulations (Albert & Young, 2005;Albert et al, 2009;Drozdov et al, 2015Drozdov et al, , 2017Shprits et al, 2006Shprits et al, , 2008Shprits et al, , 2016Shprits et al, , 2017Subbotin et al, 2010;Turner, Angelopoulos, Morley, et al, 2014;Usanova et al, 2014;Xiang et al, 2017;Xiao et al, 2010;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Their relevance to the radiation belt dynamics has been evaluated in earlier works, based either on observations or model simulations (Albert & Young, 2005;Albert et al, 2009;Drozdov et al, 2015Drozdov et al, , 2017Shprits et al, 2006Shprits et al, , 2008Shprits et al, , 2016Shprits et al, , 2017Subbotin et al, 2010;Turner, Angelopoulos, Morley, et al, 2014;Usanova et al, 2014;Xiang et al, 2017;Xiao et al, 2010;Yu et al, 2013). Their relevance to the radiation belt dynamics has been evaluated in earlier works, based either on observations or model simulations (Albert & Young, 2005;Albert et al, 2009;Drozdov et al, 2015Drozdov et al, , 2017Shprits et al, 2006Shprits et al, , 2008Shprits et al, , 2016Shprits et al, , 2017Subbotin et al, 2010;Turner, Angelopoulos, Morley, et al, 2014;Usanova et al, 2014;Xiang et al, 2017;Xiao et al, 2010;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There have been two main competing paradigms for the loss of radiation belt relativistic electrons: radial loss to the magnetopause (Shprits, Thorne, Friedel, et al, ; Loto'Aniu et al, ) and local loss to the atmosphere (Thorne & Kennel, ; Horne & Thorne, ; Summers et al, ). For the former, the primary observational evidence is the radially peaked PSD profile of relativistic electrons (Turner et al, ; Mann et al, ); for the latter, the observational evidences frequently mentioned in previous works are the wave‐related electron precipitation at low altitudes (Lorentzen et al, ; Millan et al, ; Miyoshi et al, ; Tsurutani et al, ; Breneman et al, ) and the flat‐top PAD characteristic (Usanova et al, ; Engebretson et al, ; Su et al, ; Shprits et al, ). Here on the basis of the analysis of an extreme radiation belt electron loss event observed by RBSP and POES on 27 February 2014, we present new evidence for the EMIC wave‐driven local precipitation loss of relativistic electrons in the heart of the outer radiation belt: The RBSP‐observed radial profile of the relativistic electron PSD appeared to be quasi‐monotonic, in contrast to the peaked type of previously reported events (e.g., Turner et al, ; Mann et al, ).…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Wave‐driven pitch angle scattering can reduce the altitudes of electron mirror points, and collisions with atmospheric particles yield the precipitation loss of electrons. The primary characteristic of radial loss is a radially peaked PSD profile (Turner et al, ; Mann et al, ), while the main evidences for local loss are the flat‐top PAD characteristic (Usanova et al, ; Engebretson et al, ; Su et al, ; Shprits et al, ) and the wave‐related electron precipitation observed at low altitudes (Lorentzen et al, ; Millan et al, ; Miyoshi et al, ; Tsurutani et al, ; Breneman et al, ; Zhang, Halford, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Obviously we have more than three conditional equations at hand and a solution must be found in the sense of minimizing the mean square of the residuals. The so-called normal equations (Schmucker and Weidelt, 1975) …”
Section: Combining Fluxgate and Induction Coil Magnetometermentioning
confidence: 99%
“…Electrons interacting with such waves can be scattered into the loss cone and reduce the energy content of the radiation belt. Pc-1 pulsations (f > 0.1 Hz) can be caused by electromagnetic ion cyclotron (EMIC) waves, which is the subject of many recent investigations (e.g., Shprits et al, 2016or Usanova et al, 2014.…”
Section: Introductionmentioning
confidence: 99%